Emotion Regulation Difficulties Moderate the Association Between Heavy Episodic Drinking and Dating Violence Perpetration Among College Men. Issue 9 (20th October 2016) - Stappenbeck, Cynthia A.; Davis, Kelly Cue; Cherf, Nicolas; Gulati, Natasha K.; Kajumulo, Kelly F.
ABSTRACT: Because of high rates of heavy drinking and dating violence (psychological or physical aggression toward a dating partner) among college men, we examined whether emotion regulation difficulties moderated the association between heavy drinking and dating violence perpetration. One hundred and fifty-eight men were recruited from a large northwestern U.S. university between April 2014 and August 2014. Participants completed an online survey that assessed their emotion regulation difficulties as well as their past year history of heavy episodic drinking (HED; consuming 5+ drinks in 2 hr) and dating violence perpetration. Generalized linear models revealed that the positive association between HED and dating violence perpetration was stronger for men with greater impulse control difficulties and for those who reported limited access to emotion regulation strategies. In addition to continued efforts to reduce heavy drinking among college men, interventions targeting emotion regulation difficulties should be incorporated into standard dating violence intervention and prevention efforts to further reduce the likelihood of dating violence perpetration in this population.